Perceived Diversity and Team Functioning: The Role of Diversity Beliefs and Affect. (February 2013) - Hentschel, Tanja; Shemla, Meir; Wegge, Jürgen; Kearney, Eric
Based on data from 38 organizational teams ( N = 241), we investigated the influence of perceived diversity on team identification and relationship conflict. Moreover, we examined the roles of diversity beliefs as a moderator and group affective tone as a mediator of these relationships. Objective diversity in age, gender, educational level, nationality, or tenure was not related to perceived diversity, team identification, or emotional conflict. But as hypothesized, perceived diversity was negatively associated with team identification and positively associated with relationship conflict. Diversity beliefs moderated these effects. Negative group affective tone mediated the relationship among perceived diversity, diversity beliefs, and relationship conflict. We found a similar trend for positive group affective tone with regard to the relationship among perceived diversity, diversity beliefs, and team identification. These results illustrate the central role of shared affect and diversity beliefs in determining whether work group diversity is an asset or a liability.